2013
DOI: 10.1002/rcm.6632
|View full text |Cite
|
Sign up to set email alerts
|

Chemical analysis and chemical imaging of fragrances and volatile compounds by low‐temperature plasma ionization mass spectrometry

Abstract: A semi-quantitative method has been demonstrated for the routine analysis of volatile and semi-volatile compounds. This method would be useful in quality control and production environments to determine product persistence, location of analytes and to complement olfactory studies for determining concentrations in the ambient environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Cooks and co-workers investigated the distribution of fragrances on surfaces with centimetre-scale resolution [36]. In contrast, we measured volatiles directly from biological tissues and improved both the technical spatial resolution [10,21], as well as the data visualisation.…”
Section: Spatial Distribution Of Volatiles and Semi-volatiles In Chilmentioning
confidence: 98%
“…Cooks and co-workers investigated the distribution of fragrances on surfaces with centimetre-scale resolution [36]. In contrast, we measured volatiles directly from biological tissues and improved both the technical spatial resolution [10,21], as well as the data visualisation.…”
Section: Spatial Distribution Of Volatiles and Semi-volatiles In Chilmentioning
confidence: 98%
“…The plasma is composed of reactive species including atoms, molecules, metastable ions, radicals, high‐energy photons and electrons, and is capable of ionizing analytes via proton transfer or Penning ionization . It was demonstrated that LTP‐MS could analyze compounds in the gas phase, upon solid surfaces, and from the surface of solutions, with the analytes ranging from explosives to drugs, agrochemical residues, works of art, and organic aerosol particles . Furthermore, LTP was capable of in situ monitoring of analytes from organic reactions directly in bulk solution, and detecting oxidative cleavage of disulfide bonds for peptides …”
mentioning
confidence: 99%
“…At atmospheric pressure, the nonequilibrium DBD plasma is characterized by low gas temperature of around 30°C (Harper et al, 2008). The low temperature of the DBDI and LTP plasma gas allows soft ionization of volatile organic compounds, but the detection of lowly volatile compounds has remained less effective due to the low desorption efficiency (Benassi et al, 2013; Campbell et al, 2013; Ding et al, 2018). LTP also has enabled MSI analyses of volatile and semivolatile compounds such as fragrances and flavors spotted on filter paper as well as Chinese calligraphy patterns but with spatial resolution strongly dependent on the size of the plasma stream (Liu et al, 2010; Campbell et al, 2013).…”
Section: Laser Desorption/ablation Coupled To Ambient Ionization In Bioapplicationsmentioning
confidence: 99%